1977
DOI: 10.1093/ageing/6.2.77
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Histological Assessment of Cellular Death, in Relation to Mitosis, in Rat Thymus During Growth and Age Involution

Abstract: The rates of cellular proliferation and cellular death were investigated in the rat thymus during growth and involution. It was found that the percentage of dead cells gradually increased with age, whilst the rate of cell proliferation declined, indicating that a substantial proportion of lymphocytes that divide in the thymus also die there. It was also found that there exists a density-dependent distribution pattern of mitotic and dead cells and that this distribution pattern changed with age. It is suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

1979
1979
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
3
4
1
Order By: Relevance
“…Our findings in human thymi did not confirm this assumption, but correspond to observations of HINSULL et al (1977) in aging rats. Until today, no report has come up which evidences that the majority of lymphocytes produced in the thymus die in situ.…”
Section: Cellular Proliferation and Cell Deathcontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings in human thymi did not confirm this assumption, but correspond to observations of HINSULL et al (1977) in aging rats. Until today, no report has come up which evidences that the majority of lymphocytes produced in the thymus die in situ.…”
Section: Cellular Proliferation and Cell Deathcontrasting
confidence: 99%
“…Our observation corresponds to the findings of HINSULL et al (1977). These authors observed a similar quantitative relationship between aging and spontaneous thymocyte proliferation in rats.…”
Section: Cellular Proliferation and Cell Deathsupporting
confidence: 93%
See 1 more Smart Citation
“…The choice of azo dye technique ) employing a bromine-rich reaction product also has advantages in that it allows a further extension of the method in the analytical scanning electron microscope (Bowen & Lewis, 1980a;. Hinsull et al (1977) have reported an assessment of cell death and mitosis in rat thymus during growth and age involution, using a trypan blue based method. Bowen & Ryder (1974, working on planarian worms, established the use of acid phosphatase activity as a marker for cell lysis and deletion.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the assessment of cell death and mitosis in relation to tissue dynamics is general. A quantitative histological assessment of cell death in relation to mitosis in rat thymus during growth and age involution has been presented by Hinsull et al (1977), where trypan blue was used to mark dying and pyknotic cells.…”
Section: Introductionmentioning
confidence: 99%